Impact of Elevated Temperature and Carbon dioxide on Seed Physiology and Yield - Talwar, Seema; Bamel, Kiran; Prabhavathi (Plant Science Today, 2023)
Food security is of utmost priority to humankind. This is the implication of various interconnected factors that lead to climate change. Elevated temperature and carbon dioxide levels are just 2 of these. The nutrient is an inseparable aspect of food. The change in climate is posing threat not only to the amount of available food but also to the nutrients laden in the food items. Seeds are the miniature form of plants and are a reflection of their future health and nutritional status. The changes in environmental factors predominantly challenge the growth and development of a seed. This review is an attempt to understand the impact of elevated CO2 and temperature on seed germination, the nutritional status of the seed and the yield in form of total seed production. It gives a direction for analysis and future studies that may use the latest available tools like gene editing to tackle and counteract the retarding effect of climate change on these parameters of seed, thereby offering a climate resilient agriculture.